Implementasi Model Pembelajaran Kooperatif dalam Pengajaran Bahasa Sunda di Sekolah - Puri Lestari, Tusina (Andragogia: Journal Education Science And Islamic Studies, 2024)
This study aims to explore the effectiveness of implementing a cooperative learning model in teaching Sundanese in secondary schools. The cooperative learning model, which emphasizes cooperation between students, is expected to improve students' language skills and learning motivation. The research method is a quasi-experimental study with a control and experimental group design. The results of the study indicate that the implementation of the cooperative learning model significantly improves students' speaking, writing, and understanding of Sundanese culture compared to conventional learning methods. This study provides recommendations for teachers to apply this model in learning Sundanese in order to achieve more optimal results.